Commissural NTS lesions and cardiovascular responses in aortic baroreceptor-denervated rats - Sato, Monica Akemi; Menani, José Vanderlei [UNESP]; Lopes, Oswaldo Ubríaco; Colombari, Eduardo [UNESP] (Wolters Kluwer, 1999)
Both acute (1 day) lesions of the commissural nucleus of the solitary tract (commNTS) and aortic baroreceptor denervation increase pressor responses to bilateral common carotid occlusion (BCO) during a 60-second period in conscious rats. In this study, we investigated the following: (1) the effects of commNTS lesions on basal mean arterial pressure (MAP) and heart rate (HR) of aortic denervated (ADNx) rats; (2) the effects of acute commNTS lesions on pressor responses to BCO in ADNx rats; and (3) the effects of chronic (10 days) commNTS lesions on the pressor response to BCO. ADNx increased basal MAP and HR in sham-lesioned rats. Acute commNTS lesions abolished the MAP and HR increases observed in ADNx rats. Acute commNTS lesions increased the pressor responses to BCO in rats with intact- baroreceptor innervation but produced no additional change in the pressor response to BCO in ADNx rats. Chronic commNTS lesions did not change the pressor responses to BCO in rats with intact-baroreceptor innervation. The data show that acute commNTS lesions abolish the MAP increase produced by aortic baroreceptor denervation. They also suggest that acute commNTS lesions enhance the pressor response to BCO by partial withdrawal of aortic baroreceptor inputs into the NTS. Chronically, reorganization in the remaining aortic baroreceptor or in the baroreflex function as a whole might produce normalization of the cardiovascular responses to BCO.
Keywords: Baroreceptors; Blood pressure; Chemoreceptors; Occlusion; Solitary nucleus; animal experiment; animal model; aorta pressoreceptor; blood pressure regulation; carotid artery obstruction; mean arterial pressure; solitary tract nucleus; Aorta; Blood Pressure; Carotid Arteries; Denervation; Heart Rate; Pressoreceptors; Rats, Wistar; Solitary Nucleus